If it's not what You are looking for type in the equation solver your own equation and let us solve it.
60=4(5-x)
We simplify the equation to the form, which is simple to understand
60=4(5-x)
Reorder the terms in parentheses
60=+(+20-4x)
Remove unnecessary parentheses
+60=+20-4x
We move all terms containing x to the left and all other terms to the right.
+4x=+20-60
We simplify left and right side of the equation.
+4x=-40
We divide both sides of the equation by 04 to get x.
x=-10
| 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 | | -n+n= | | 2(4z-2)-2(5-3z)=4 | | 5x+5=4x+4 | | 11+2(3n-11)=1 | | 6((2n^2)+3n-35)=0 | | (3x+4)-30=0 | | t-45=-48 | | 4x+8y-3x+2y= | | 1x+2y=18 | | 12+3(z-4)=-5z+5 | | -3(x+12)=16-x | | -6(n+3)+21=-3n-6 |